Cardiovascular risk in patients with rheumatoid arthritis - N M Nikitina; A P Rebrov; N M Nikitina; A P Rebrov (Терапевтический архив, 2009)
Aim. Cardiovascular risk determination in patients with rheumatoid arthritis (RA) on the basis of standard and new risk factors (RF). Material and methods. Incidence of standard cardiovascular RF was studied in 312 RA patients and 57 healthy controls. Overall coronary risk (OCR) and cardiovascular death risk (SCORE scale), coronary heart disease risk (Framingem scale) were analysed. In addition, such RF as severity of systemic inflammation, some hemostatic indices, arterial wall stiffness were assessed. Results. Arterial hypertension (AH) occurred in 63.5% and hypercholesterinemia in 57.7% patients. AH in RA males is detected significantly more often than in population while blood lipid composition is satisfactory because of high HDLP cholesterol. The Framingem index in RA patients is lower than in the controls (7.7 ± 5.4 and 9.4 ± 9.3%), mean SCORE was 2.16 ± 2.9% (17.3% patients had high SCORE), a high OCR was registered in 25.7%. High level of C-reactive protein, platelets (320 Ѕ 109/l), hyperfibrinogenemia were found in 70.2, 31.1% and 55.9% patients, respectively. RA is accompanied with high activity of Willebrand factor, a low level of antithrombin III, suppression of fibrinolysis in blood plasm (p < 0.05). This reflects high thrombogenic blood potential, high risk of thrombosis and related complications of coronary heart disease. Aortic pulse wave velocity over 12 m/s was recorded significantly more frequently in RA than in control patients (p < 0.001), RA females had high arterial rigidity both in the periphery and aorta. Conclusion. Cardiovascular risk indices based on standard RF cannot assess the risk in RA patients. Additional factors should be taken into consideration: severity of inflammation, hemostasis, arterial stiffness.